New campus-Marshall J. Fiese Health Center-0001
Four well-Equipped physican's suites, physiotherapy and X-ray rooms, nurse's work and treatment rooms, and a modern laboratory make up the medical units in the Health Services building. With the sdvent of Residence Halls an infirmary will be added to the present structure. One full time and 13 part-time physicians, four full-time nurses, and one laboratory technician are employed in the health center.